Analisis Perbedaan Tindak Pidana Pencurian Pada KUHP (Kitab Undang-Undang Hukum Pidana) Baru dan Lama - M, Mulyadi; Wahdah, Azzhara Nikita; Anindya, Salma Elsa; Syalsabila, Khairunnisa; A, Annisa; Anisah, Aura; Nirwana, Rena Putri; Tambunan, Joy Catherine Carina; Manullang, Halim (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Theft is the most prevalent crime in society. It involves an individual unlawfully taking property, either in whole or in part, from someone else with the intent to own it illegally. The crime of theft itself is recognized in law and is a type of crime against individual interests that harms other people and the surrounding community. The Criminal Code (KUHP) strictly prohibits these crimes and emphasizes that violators will be subject to detailed and severe punishments. This is manifested in the form of punishment or threats of punishment imposed. In the Old Criminal Code (KUHP) and the New Criminal Code (KUHP) regarding the crime of theft, actually there has not been a very big change, where there are differences in the articles, but in this case the substance and interpretation are still unclear. too different. Then there are also added types of criminal acts of theft and also differences related to criminal threats for each type of theft act. This journal studies further the differences between criminal acts of theft in the old Criminal Code (KUHP) and the new Criminal Code (KUHP).